ELASTISITAS, SKALA EKONOMI DAN EFISIENSI PRODUKSI BUDIDAYA IKAN BANDENG PADA SENTRA PERIKANAN DI TAJUNG WIDORO DESA MENGARE KABUPATEN GRESIK - Dini Atika Najah; Riniati Riniati; Fajar Wahyu Prianto (Relawan Jurnal Indonesia, 2019)
This study aims to determine how the production elasticity, scale of production and production efficiency in milkfish production in Mengare, Gresik. The research method used is descriptive method and collegial method. The selection of the research area was done purposely (Purposive Sampling Method) in Mengare Village, Gresik Regency. The population in this study is that all the business of milkfish ponds in the village of Mengare are incorporated into a container organization that partners with the fisheries service in Gresik Regency. The population of noble milkfish members is 522 fishermen, 40 fishers were taken as samples. The data analysis method used in this study is the method of multiple linear regression analysis, calculation of economies of scale and calculation of production efficiency. The hypothesis test used is the t test, F test and coefficient of determination. The results showed that the results of panel data regression analysis showed that elasticity in milkfish production was inelastic. Based on the results of the calculation of business income in the three processing groups. The ratio of receipts to total costs on small and large scale processors, each of the Cost Ratio of fishermen is calculated by comparing total revenues / total costs so that the value of the business scale of 1 - 5 ha is 2.6, the business scale is 6-10 ha of 3.7 and business scale 11-15 ha of 3.9